A characteristic-based sorting tool for SLP beneficiaries - Celia M. Reyes; Arkin A. Arboneda (Philippine Institute for Development Studies (PIDS), 2018)
The Sustainable Livelihood Program (SLP) is one of the social protection programs of the Department of Social Welfare and Development (DSWD) that aims to provide livelihood opportunities to its targeted beneficiaries. The program offers two tracks of assistance, employment facilitation and microenterprise development. This study aims to develop a characteristics-based sorting tool that assesses the best suited track for a participant using personal and background information, personality and characteristics of the community. This offers a more systematic way of assessing and doing track selection vis-à-vis the current system letting the participants choose based primarily on their preferences. Logit estimations were performed using a survey of 2015 SLP beneficiaries to estimate the probability of success for each track using individual and community variables.
Keywords: 330; Department of Social Welfare and Development (DSWD); Sustainable Livelihood Program (SLP); employment facilitation; microenterprise development; sorting tool